Seismic Data compression using 2D Lifting-Wavelet algorithms (2014)
Different seismic data compression algorithms have been developed in order to make the storage more efficient, and to reduce both the transmission time and cost -- In general, those algorithms have three stages: transformation, quantization and coding -- The Wavelet transform is highly used to compress seismic data, due to the capabilities of the Wavelets on representing geophysical events in seismic data -- We selected the lifting scheme to implement the Wavelet transform because it reduces both computational and storage resources -- This work aims to determine how the transformation and the coding stages affect the data compression ratio -- Several 2D lifting-based algorithms were implemented to compress three different seismic data sets -- Experimental results obtained for different filter type, filter length, number of decomposition levels and coding scheme, are presented in this work